RESPONSE OF ABELMOSCHUS ESCULENTUS L. FORINOCULATION WITH MYCORRHIZAE AND FOLAIR APPLICATION WITH BIO-STIMULATORS AND EFFECT ON VEGETATIVE GROWTH CHARACTERS - & et al., AL-Samarai (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The current study was carried out at the Fields belongs of Horticulture Department, Collage of Agricultural Engineering Science, University of Baghdad, Al-Jadiriyah for the spring season 2016 -2017 to study the effect for inoculation mycorrhizae and folair application with bio stimulators and their interaction in the growth characters of (local okra ptera). A factorial experiment (2 in randomized complete block design (RCBD), the experiment included (12) treatment Distributed in three replicates. The three factors used in this experiment included . The inoculation with control (C) Mycorrhizae ( M ) , Biozyme (B ) ( B1 2cm3.L-1), ( B2 4cm1-.L-1) , Phosphalas (P) (P 2cm3.L-1), ( M + B1), ( M + B2), (P + M ), ( P + B1), (P + B2), ( M + P + B1), ( M + P + B2). The data were analyzed according to the design followed and the mean was tested by the lowest significant difference at 0.05%. The results showed a significant increase in the studied traits . The results showed that the three factors and their interactions had significant effects on most of the growth characters measured. The inoculation with the Mycorrhizae , Biozyme and Phosphalas was superior in giving higher values of plant height (M1B2P1) 120.00 cm, Main branches number per plant 13.00, number of leaves 197.0 (Leaf .plant -1), leaf area 394.0 (dcm2. Leaf ), fresh weight of vegetative 3200 (kg. plant-1) Dry weight of vegetative 209.0 ( g . plant-1), number of nodules on the stem 41.33 (nod. plant -1), relative chlorophyll content (SAPD) respectively. The M1B2P0 combination treatment recorded the highest values of secondary branches number per plant 10.33. The M1B1P0 treatment recorded the highest values of diameter of stem 4.03 (cm).